العلمانية في الفكر العربي: قراءة في إسهامات المسيحيين الأوائل في عصر النهضة العربية - الياسرى، يونس عباس نعمة (جامعة بابل - مركز بابل للدراسات الحضارية والتاريخية, 2021)
يجمع الباحثون أن من أهم أسباب انطلاقة عصر النهضة العربية في القرن التاسع عشر في مختلف توجهاته الفكرية، كان الاطلاع عن قرب على ما توصلت إليه الحضارة الغربية الحديثة ولاسيما بعد الاحتلال الفرنسي لمصر وبلاد الشام، بعد أن مهدت للتعرف على التطورات الفكرية والعلمية في مختلف المجالات التي شهدتها فرنسا قبل وبعد ثورتها العالمية سنة ١٧٨٩ ومختلف القراءات لذلك الاحتلال تجمع أنه أحدث صدمة ليس في مصر وإنما في البلاد العربية لاسيما في بلاد الشام، والدليل على ذلك التعاون مع فرنسا بعد انسحابها وأرسال البعثات العلمية وتأسيس المطابع والنشاط الفكري والثقافي والتعليمي الغير مسبوق في البلاد العربية فكان حقا أن يطلق عليها مصطلح النهضة العربية في كل توجهاتها المختلفة. تمحور الانفتاح الغير مسبوق على الحضارة الغربية بثلاث اتجاهات نهضوية الأول طالب بالإفادة من الحضارة الغربية دون قيد أو شرط ومحاولة الانقطاع عن ماضي الأمة الذي تمثله الدولة العثمانية ومن أبرز سماته التخلف والجهل والاستبداد، وقرأ الاتجاه الثاني الموضوع بشكل مختلف وطالب التوفيق بين التراث وماضي الأمة والإفادة من الحضارة الغربية بما يناسب تطلعات البلاد العربية في التقدم والرقي واللحاق بركب الحضارة، فيما رفض الثالث الإفادة من الحضارة الغربية وعدها حضارة مادية أهم أغراضها السيطرة على البلاد العربية ونهب خيراتها وطمس ثقافتها لاسيما الدينية ووجهت تهم الإلحاد والكفر إلى أبرز مفكري عصر النهضة الأوربية ومن أيد أفكارهم بقوة وطالب بتطبيقها على البلاد العربية. أهم المواضيع الخلافية نتاج الفكر النهضوي هي العلمانية، لاسيما في معالجتها لنظام الحكم والدين والسياسة ومبدأ الحريات وحقوق الإنسان وأول من تصدى لها جملة من المفكرين العرب المسيحيين في بلاد الشام، هذه الورقة البحثية تناقش الأفكار التي قدمها وناقشها عدد منهم بعيدا عن الانتماء الطائفي والقول بالتخوين والتكفير والإلحاد، والبحث عن همهم وهل كان هم الأمة جميعا في التخلص من تبعات الجهل والتخلف والاستبداد؟ والبحث عن المشتركات التي تجمعنا والابتعاد عما يفرقنا؟ ونحن بأشد الحاجة إلى نهضة فكرية جديدة تنقذنا من هذا السبات والفراغ الفكري وطغيان الاستبداد السياسي والمالي المدعوم إعلاميا لتمزيق الأمة أكثر مما هي ممزقة، لذلك علينا الإفادة من دروس النهضة العربية في القرن التاسع عشر ومراجعاتها والتي أول حلقاتها المهمة الفكر المسيحي ورؤيته النهضوية.
The researchers mentioned that one of the most important causes of the Arab renaissance in the nineteenth century in its various intellectual orientations was to closely examine the findings of modern Western civilization, especially after the French occupation of Egypt and the Levant. The thinkers were briefed on the intellectual and scientific developments in the various fields that France witnessed before and after its world revolution in 1789, and the various readings of that occupation in Egypt unite that it brought about a shock not in Egypt but in the Arab countries, especially in the Levant, and the evidence for that cooperation with France after its withdrawal and dispatch The scientific missions, the establishment of printing presses, and the unprecedented intellectual, cultural and educational activity in the Arab countries, so it was truly to be called the term Arab renaissance in all its different orientations. The unprecedented openness to Western civilization represented three renaissance trends. The first called for benefiting from Western civilization without restriction or condition and trying to cut off from the nation’s past represented by the Ottoman Empire. Its most prominent features are backwardness, ignorance and tyranny. The second trend read the topic in a different way and demanded reconciliation between heritage and the nation's past and benefiting from Western civilization in a way that suits the aspirations of the Arab countries in progress, advancement and catching up with civilization, while the third refused to benefit from Western civilization, considering it a material civilization whose most important purposes are to control the Arab countries, plunder their resources and obliterate their culture, especially Religious charges of atheism and infidelity were directed at the most prominent thinkers of the European Renaissance and those who strongly supported their ideas and demanded their application to the Arab countries. The most important controversial issues resulting from renaissance thought are secularism, especially in its treatment of the system of governance, religion, politics, the principle of freedoms and human rights, and the first to address it a group of Arab Christian thinkers in the Levant This research paper discusses the ideas presented and discussed by a number of them away from sectarian affiliation and the saying of treason, blasphemy and atheism, and the search for their concern. Was it the concern of the whole nation to get rid of the consequences of ignorance, backwardness and tyranny? And the search for the common ones that unite us and stay away from what separates us? We are in dire need of a new intellectual renaissance that saves us from this hibernation, intellectual vacuum, and the tyranny of political and financial tyranny supported by the media to tear the nation apart more than it is torn apart. Therefore, we must benefit from the lessons and reviews of the Arab Renaissance in the nineteenth century, whose first important episodes are Christian thought and its renaissance vision.
Keywords: الفكر العربي -- النهضة العربية -- العلمانية العربية -- المسيحيون العرب